The labor market in South Africa, 2000-2017 - Jacqueline Mosomi; Martin Wittenberg (IZA World of Labor, 2020)
The South African economy was on a positive growth trajectory from 2003 to 2008 but, like other economies around the world, it was not spared from the effects of the 2008 global financial crisis. The economy has not recovered and employment in South Africa has not yet returned to its pre-crisis levels. Overall inequality has not declined, and median wages seem to have stagnated in the post-apartheid period. Labor force participation has been stable and although progress has been made, gender imbalances persist.
Keywords: J15; J16; J31; J7; 330; employment; real wages; inequality; South Africa